GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 644376824 species occurrences available in GBIF matching the query: All data. The dataset includes 644376824 records from 13637 constituent datasets: 71 records from Bolzplatz. 1 records from Pelops torulosus. 1 records from Oribates badius. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 48944 records from Grey seal at-sea distribution 2009-2014. 315232 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 11806 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 244284 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 97 records from DMNH Eggs. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 6543 records from University of Ghent - Zoology Museum - Vertebratacollectie. 10730 records from kpabg_lichens. 22137 records from Global compendium of Aedes albopictus occurrence. 53985 records from BioMar - LIFE project. 116410 records from Naturalis Biodiversity Center (NL) - Crustacea. 6 records from Hemichordata collection of National Museum of Nature and Science. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 123 records from Bryozoa of the British Isles. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 336 records from Macroarthropods, Isua 2013, Greenland. 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 775 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 447 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 31917 records from Mollusca of Costa Rica (INBio). 57218 records from National Biodiversity Data Bank. Observation records, 1900-2014. 373 records from Otter survey of Ireland 2004 & 2005. 3105 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 1 records from Arthropoden aus südostalpinen Höhlen.. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 5549 records from Diplopoda (NSMK-DI). 8857 records from Artròpodes d'Andorra. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 58475 records from Oregon State University Herpetological Collection. 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 468 records from Chironomid Specimen records in the Chironomid DNA Barcode Database. 3633 records from Bioimages. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 15100 records from Northern Ireland Mammal Database. 398 records from Tsetse flies of East Africa update. 375 records from Phthiraptera. 153480 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 8748 records from British Lichen Society - BLS Rare and Threatened Lichen Records: Wales. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 5953 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 468533 records from Royal Dutch Angling Association (SVN) - Piscaria. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 16 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rostratulidae. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 5 records from Arthropoden aus südostalpinen Höhlen.. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 3 records from A new species of the genus Ectemnius Dahlbom, 1845 from Cameroon (Hymenoptera: Crabronidae). 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 24 records from A revision of the Indo-Pacific fish genus Caragobius (Gobiidae: Amblyopinae).. 1 records from Nothrus spinifer. 3509 records from Entocytheridae (Ostracoda) World Database. 8220356 records from OEH Atlas of NSW Wildlife. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 12161 records from ISE - Herbário ISE. 156156 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 215 records from The Diptera Site. 10072 records from Guadeloupe_Herbier. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 28385 records from Plan de vertebrados de la Patagonia. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 2312 records from Mycological collection of the National Museum. 457 records from Microbial Observatory of the Laboratoire Arago. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 21975 records from HUEM - Herbário da Universidade Estadual de Maringá. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 111784 records from Jordal. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 1485 records from IWDG Constant Effort Cetacean Sighting Scheme. 13577 records from JOI - Herbário Joinvillea. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 1650 records from University of Calgary Herbarium. 27 records from Redescription of Apteronotus mariae (Eigenmann & Fisher, 1914) and the taxonomic status of Apteronotus jurubidae (Fowler, 1944) (Gymnotiformes: Apteronotidae).. 31 records from Siphonaptera. 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 59016 records from Biological Records Centre - Isopoda (Interim dataset). 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 43 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 83 records from Eden Rivers Trust - White-clawed crayfish (Austropotamobius pallipes) distributions within four sub-catchments of the River Eden Catchment, Cumbria 2007-2008. 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 5709 records from Coleoptera of Piska Forest. 379 records from WNMU Fish Collection (Arctos). 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 26534 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 5826 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 51 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 2546 records from The atlas of butterflies in Kraków. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 1303 records from Mid Ulster Hare Surveys 2012-2015. 12279 records from ISM Mammalogy Collection. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 99300 records from Landesmuseum Kärnten. 115 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 5796 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 51110 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie in Flanders, Belgium. 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 9543 records from RSPB - Wader survey on Uist in 2007 (RSPB/BTO). 330041 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 7735 records from CSUC Vertebrate Collection. 380 records from USGS SESC - Biscayne - Herpetofauna - 2002-2003. 10358 records from Census of the flora of Benin. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 1741 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 191 records from Herpetofauna laguna El Tinije. 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 8934780 records from Botanical Society of the British Isles - Vascular Plants Database. 1238 records from Insect Collection (CeStuBio). 1 records from Celaeno plicata. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 20 records from Heteroptera - SMNG. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 13912 records from Fishes in MZNA-VERT: freshwater communities in the Larraun river (Spain). PhD project, Javier Oscoz & Master project, A. Cos.. 20 records from Truchas Mexicanas. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 67914 records from HUFU - Herbarium Uberlandense. 1 records from Hoplophora globosa. 9 records from A new species of the genus Aphanius (Nardo, 1832) (Actinopterygii, Cyprinodontidae) from Algeria.. 1030627 records from Phanerogamic Botanical Collections (S). 10000 records from National Lesser Horseshoe Bat Database. 20043 records from Mollusca collection of National Museum of Nature and Science. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 90189 records from African Rodentia. 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 14379 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 62283 records from PRECIS (KwaZulu-Natal Herbarium). 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 33 records from Revision von Suctobelba trigona (Michael, 1888). 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 3 records from MSB Mammal Observations (Arctos). 268764 records from MVZ Herp Collection (Arctos). 28702 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 1 records from Un chilopode cavernicole nouveau de Yougloslavie Bothropolys magnificus n. sp.. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 37 records from Museu Paraense Emilio Goeldi - Schizomida Collection. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 28924 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 65 records from A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina.. 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 4108 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 115324 records from University of Vienna, Institute for Botany - Herbarium WU. 1 records from Damaeus concolor. 712 records from Herbier G. Garapin (BOUM). 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 9889 records from uconn-mammals. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 10633 records from Biological Records Centre - Collembola Recording Scheme. 1702 records from BioGIS - Bryophytes - HUJ collections. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 159 records from University of Amsterdam (NL) - Páramo vegetation research, Venezuela.. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 1205 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 3592 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 9302 records from Ants from the Paraguayan dry Chaco. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1 records from Nothrus runcinatus. 38543 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 38652 records from Marine species distributions in Irish coastal waters. 1998 records from Aves de la cuenca media del río Bogotá. 3806 records from USGS SESC - Everglades - Herpetofauna - 2005. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 16636 records from UFG - Herbário da Universidade Federal de Goiás. 5 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 1592 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Furnariidae. 326 records from Colección nacional de palmas de Colombia - JBQ. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 610 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 4 records from New data on recently described rodent species Paulina's Limestone Rat Saxatilomys paulinae Musser, Smith, Robinson & Lunde, 2005 (Mammalia: Rodentia). 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 232262 records from MVZ Mammal Collection (Arctos). 8136 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coelenterata. 10075 records from Nematoda of Costa Rica (INBio). 1 records from Zetes longiusculus. 3204 records from Faunal Inventory of Morysin Nature Reserve. 89874 records from ecoscope_observation_database. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 4343 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 561820 records from Bee Biology and Systematics Laboratory. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 2494 records from Colección de peces dulceacuícolas de Costa Rica. 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 170316 records from Australian National Wildlife Collection provider for OZCAM. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 288 records from Fungi of Słowiński National Park, Poland. 412 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Columbidae. 353 records from Coastal and marine species. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 184364 records from LACM Entomology Collection. 167 records from Faunistic diversity of spiders (Araneae) in Galichitsa mountain (FYR Macedonia). 22049 records from Tromsø Museum, Bryophytes. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 356 records from Morphologische Daten von Puffinus creatopus. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 34 records from New records in vascular plants alien to Kyrgyzstan. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 511 records from Coleoptera of Swierklaniec Forest. 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 7 records from Additions to the Genus Phyllodesmium, with a Phylogenetic Analysis and its Implications to the Evolution of Symbiosis. 3103 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 12370 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 741967 records from PlutoF platform observations. 35 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 1020 records from Irish Marine Turtle Database. 859 records from Extra-andean Patagonian Herbarrium -CONICET- Argentina. 15637 records from CCBER Herpetology Collection. 52448 records from IAC - Herbário do Instituto Agronômico de Campinas. 9788 records from SANT-Lich. 60672 records from QLD DERM Coastal Bird Atlas (Trial). 51390 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 23052 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 4734 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 4 records from Fossil (SMNH-FO). 55431 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 1 records from Egg capsules of Atlantoraja cyclophora (Regan, 1903) and A. platana (Günther, 1880) (Pisces, Elasmobranchii, Rajidae).. 8332 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 568 records from Coleccion Paleoinvertebrados CCT Mendoza - CONICET. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 2116 records from Collection entomologique Pierre Lachiver. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 13597 records from Orthopteroidea. 38187 records from Online Atlas of vascular plants 2012-2020. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 7427 records from Weevils of the Tatra Mts.. 88901 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 458185 records from Bird Atlas 2007 - 2011. 3082 records from dec2011. 2007 records from Palaeobiology collection, FAU Erlangen. 2 records from Two New Jumping Spiders of the Genus Chalcoscirtus from China (Araneae: Salticidae). 121225 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 1 records from Oribates calcaratus. 8 records from Order Diptera, family Mydidae. 78 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: géneros Saltator & Saltatricula. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 4424 records from Portuguese Seaweeds. 10102 records from Herbarium Vonderau - FULD. 13583 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 1284 records from Collection of Heteroptera. 3 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 9836 records from Censo de aves acuáticas invernantes de la Comunidad Autónoma del País Vasco. 2 records from A new phreatic catfish of the genus Phreatobius Goeldi 1905 from groundwaters of the Itenez River, Bolivia (Siluriformes: Heptapteridae).. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 35325 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 296072 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 177466 records from CAS Entomology (ENT). 810 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 485 records from National Taiwan Ocean University. 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 111 records from Birdrace-Uhulogen-Lippe. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 1413216 records from AntWeb. 7251 records from All Ireland Marsh Fritillary Database. 834 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 26 records from Description of a new cyprinid species, Labeo meroensis n. sp. (Teleostei: Cyprinidae), from the River Nile.. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Aramidae. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 11 records from The larvae of Hydropsyche rhadamanthys Malicky 2001 and Hydropsyche sarpedon Malicky 2001 (Trichoptera: Hydropsychidae), endemics of Crete (South Aegean, Greece), with notes on their ecology. 5733 records from Small Mammal Research Database. 4686 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 1 records from Red list project inventory, bryophytes. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 2421 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 2 records from Postia alni Niemelä & Vampola (Basidiomycota, Polyporales) – member of the problematic Postia caesia complex – has been found for the first time in Hungary. 42659 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 4579 records from Herbarium WRSL, Flora of the Silesia. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 64 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 2 records from Papakula and Hesydrimorpha: how two spider genera were described from the same species collected from the same locality (Araneae: Pisauridae). 3 records from A distinctive new species of gnatcatcher in the Polioptila guianensis complex (Aves, Polioptilidae) from western Amazonian Brazil. 259949 records from Zoology (Museum of Evolution - Uppsala). 2258 records from Biological Records Centre - Muscidae (Diptera) records from Britain and Ireland to 1985. 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 4918 records from Otter in coastal areas - Carcasses. 1 records from Lissotes working-group. 4719911 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from Oribates fuscipes. 1 records from The larva and prepupa of Eupareophora exarmata (Thomson, 1871) (Hymenoptera, Tenthredinidae). 1 records from Zetes cespitum. 13253 records from CHAS Ornithology. 7 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Nothrus segnis. 1 records from Hoplophora ferruginea. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 6237 records from Plecoptera. 62 records from The North American spider genera Paratheridula, Tekellina, Pholcomma and Archerius (Araneae: Theridiidae). 1196 records from Entomological collection of the National Museum. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 22804 records from TCWC Marine Invertebrates. 122 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 2509 records from Type Specimen Database of Museum and Institute of Zoology PAS. 28626 records from SANT-Algae. 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 2494 records from Marine Environmental Monitoring - Marine Turtles. 1 records from Celaeno obsoleta. 13094 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 389 records from Amphibian and Reptilian (KIEE-AR). 100 records from Brock University Herbarium (BU). 359 records from Herbarium Senckenbergianum (GLM) - Lichenes. 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 26880 records from KUBI Ornithology Tissue Collection. 47875 records from SPSF - Herbário Dom Bento José Pickel. 76 records from A new species of Fidelia Friese, 1899 (Hymenoptera, Megachilidae), with a key to the species of the genus. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 10137 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 1219 records from Dutch Butterfly Monitoring Indexes. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 1866 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 190 records from Relative abundance of ostracods in sediment core Sv09. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 5505 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 8 records from Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia.. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 127513 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 1124142 records from PRECIS. 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 2 records from Scaphisoma poussereaui sp. nov. from La Réunion (Coleoptera: Staphylinidae: Scaphidiinae), arange extension of the S. tricolor species group. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 33070 records from CSIRO Ichthyology provider for OZCAM. 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 239 records from Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae).. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 1201 records from monocotyledonous_geophytes_of_fergana_valley. 1678 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 934424 records from Fishbase. 5194 records from SMNS Palaeontological collection - Amber and fossil insects. 239 records from Irish Federation of Sea Anglers Catch Data. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 6541 records from Likona Invertebrates. 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 3503 records from CSIRO, Cruise SS200705, Benthic Biodiversity, Northwest Australia, 2007. 6 records from Histoire naturelle des Hymenopteres. Deuxieme partie: Les Formicides.. 4766 records from Paläontologie Marburg. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 17618 records from BioGIS - Mammals - INPA database. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 51225 records from SPF - Herbário da Universidade de São Paulo. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 6 records from Collection Myriapoda - SNSD. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 1 records from Oribates gilvipes. 94696 records from Dutch Centre For Field Ornithology (SOVON) - Breeding Bird Monitoring Program. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 116995 records from Occurrence records of southern African aquatic biodiversity. 5331 records from bird. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 28788 records from EPA River Biologists data. 2338 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 7693 records from NHM, Heteroptera. 965 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 25 records from Hyolithen - SMF. 16 records from Taxonomic review of the genus Wasmannia.. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 5793 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Haematopodidae. 8 records from A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique.. 66722 records from SANT herbarium vascular plants collection. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 2513 records from Carabidae of the Tatra Mts.. 9349 records from Harriet Irving Botanical Gardens (HIBG). 1 records from Miriapodi di alcune grotte della Campania. 145959 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 2 records from The Persian / Arabian Gulf's sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae).. 2 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 166781 records from KUBI Mammalogy Collection. 15 records from Projeto Abrace o Boto Cinza. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 624 records from Collection of botanical drawings by Georg Schweinfurth at B. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 2731 records from Collection du Musée d'Histoire Naturelle de Nice. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 3535 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 5 records from First records of Pseudodoros nigricollis Becker (Diptera: Syrphidae) from Cyprus. 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 959 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 8 records from New species of the catfish genus Trichomycterus (Siluriformes, Trichomycteridae) from the headwaters of the rio São Francisco basin, Brazil.. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 12808 records from WIWO (NL) - Migration of Pacific Golden Plovers through North-Eastern Mongolia. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 99 records from French national collection of Solanum tuberosum. 4447 records from Lepidoptera (Observations). 18521 records from Species plots from the Norwegian Vegetation Mapping Programme. 2 records from Apistogramma eremnopyge, a new species of cichlid fish (Teleostei: Cichlidae) from Peru.. 444 records from Insect Collection from New Caledonia. 77152 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Hoehlen. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 12 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 99463 records from NPL collections. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 57306 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from new species of the fungus-farming ant genus Mycetagroicus Brandao & Mayhe-Nunes A new species of the fungus-farming ant genus Mycetagroicus Brandao Mayhe-Nunes (Hymenoptera, Formicidae, Attini).. 45899 records from UFP - Herbário UFP - Geraldo Mariz. 3447 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 7509 records from Perot Museum of Nature and Science. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 9216 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_NL. 61 records from Registros restauración ecológica- Magdalena medio. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 654 records from Helgeland Museum, Tabanidae. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 372 records from Colección de Entomología - Arthropoda. 268 records from mcme_uplb_museum_plant_collection. 702 records from HSU Vertebrate Museum Reptile Collection. 3182 records from Finnish Entomological Database: Heteroptera. 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 1706 records from University of Amsterdam (NL) - Páramo pollen reference collection. 558 records from Mammals in MZNA-VERT: skull and teeth development in Rattus and Mus. 77 records from Empria and Monsoma in Japan. 38 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 612934 records from Waarnemingen.be - Butterfly occurrences in Flanders and the Brussels Capital Region, Belgium. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 1636 records from Mammal Recording Scheme, 1970-85. 387501 records from Species data extracted from the National Vegetation Database. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 2247562 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 26835 records from Herbario Pontificia Universidad Javeriana. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 52 records from New data on the jumping spiders of the subfamily Spartaeinae (Araneae: Salticidae) from Africa. 2011 records from Local BioBlitz Challenge 2013. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 94709 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 51969 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 660 records from VMNH Invertebrate Paleontology. 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 47499 records from Sphaeroceridae Collection. 409 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 7 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Melanopareiidae. 73975 records from Palaeozooloical Collections (PZ), Swedish Museum of Natural History (NRM). 146 records from Checklist of aquatic and marshy Monocotyledons from the Araguaia River basin, Brazilian Cerrado. 10606 records from Cercle des mycologues de Montréal Fungarium (CMMF). 188781 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 318 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 1329 records from API_CRSN_Data. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 4844 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 2090 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 7671 records from HERBAM - Herbário da Amazônia Meridional. 2174 records from MLZ Mammal Collection (Arctos). 113784 records from ICN - Herbário do Instituto de Ciências Naturais. 50317 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 4490 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 26 records from A new species of Chondrostoma Agassiz, 1832 (Cypriniformes: Cyprinidae) with sexual dimorphism from the lower Rio Tejo Basin, Portugal.. 68304 records from IICT Herbário LISC. 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 36974 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 414051 records from Entomology, Natural History Museum, University of Oslo. 900522 records from FLORIVON. 111802 records from Highland Biological Recording Group - HBRG Insects Dataset. 19127 records from Biological Records Centre - Cerambycidae Dataset. 2 records from Note sur les fourmis du Musée Zoologique de l'Académie Impériale des Sciences à St. Pétersbourg.. 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 3257 records from fundiv france database. 1 records from Eremaeus hepaticus. 110660 records from The avian collection at the Natural History Museum, Oslo, Norway. 1004 records from National Museum of Marine Biology and Aquarium. 798 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 2 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 157566 records from Lund Museum of Zoology - Insect collections (MZLU). 1210 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 88771 records from URM - Herbário Pe. Camille Torrand. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 85003 records from Herbario Universidad de Antioquia (HUA). 40 records from Inventario de Herpetología en el Área Sujeta a Acuerdos de Conservación Voluntaria Quebrada Aguazula, Rincón del Soldado, Yopal. 3 records from Note su alcune specie di chilopodi della regione palestinese. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 634257 records from Inventario Español de Especies Terrestres (MAGRAMA). 751 records from Trichoptera (caddisflies) of Ireland. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 1 records from On centipedes (Chilopoda) of Albania, 2. 75648 records from University of Alberta Vascular Plant Herbarium (ALTA). 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 4501 records from Colección de Mamíferos del Centro Nacional Patagónico. 1 records from Hoplophora decumana. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 44 records from Solanum_baretiae. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 1 records from Cepheus latus. 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 652 records from Spider species diversity from wet and dry habitats. 530 records from Collection Crustacea - KAUMM. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 6817 records from Colección de Reptiles del Instituto Alexander von Humboldt. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 61981 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 13993 records from Herpetology. 6258 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 3779762 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 179 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cuculidae. 10620 records from CSIRO, SRFME, Algal Biomass, Perth region, Southwest Australia, 2003-2005. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 173415 records from Hymenoptera specimen database of Kyushu University. 1 records from Dolistenus menozzii n. sp. della famiglia Platydesmidae (Miriapodi Colobognati); e altri miriapodi della Calabria. 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 1 records from Oribates flammula. 4 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 2392 records from Fongs d'Andorra. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 146 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 255 records from Inventario de Plantas Mámbita. 663 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 956 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 6855 records from Echinoderm collection of National Museum of Nature and Science. 1 records from Oribates picipes. 1 records from Arthropoden aus südostalpinen Höhlen.. 9054 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 13086 records from Collection of Coleoptera. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 51181 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 253105 records from Lyman Entomological Museum (LEMQ). 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 202 records from BTCV Scotland - BTCV wildlife counts recording workshops. 39 records from University Marine Biological Station Millport - 1995 EC Study Contract Clyde Sea Nephrops Stock Assessment Study. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 52 records from Isotope tracer experiment: meiofauna counts. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 374 records from published_chenopodium_vulvaria_observations. 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 5053399 records from Southern African Bird Atlas Project. 16749 records from IMOS - AusCPR: Phytoplankton Abundance. 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 1643239 records from SA Flora (BDBSA). 130059 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 9173 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 4266 records from UAFMC Birds. 60344 records from AM: Freshwater Invertebrates (1900-2005). 303 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 63 records from (Data S1) Palynology of ODP Site 119-739. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 2576 records from Hosted Invertebrate Collection 01. 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 26 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 1481 records from Reptilia notes, NTNU, Trondheim. 24945 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 7403 records from Fishes in MZNA-VERT: freshwater fishes of Hidalgo state (Mexico). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 41 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 585 records from Ascomycetes of Russian Fennoscandia. 119366 records from The digitization of plant specimens of NTU. 8164 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 5850 records from UAFMC Fish. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 1359 records from Polychaetes from two subtidal rocky shores of the North coast of Crete, collected for the NaGISA project 2007-2008. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 86556 records from NINA Vanndata øvrige arter. 77 records from Xiphosura collection of National Museum of Nature and Science. 80128 records from NCSM Fishes Collection. 365 records from Colección Herpetológica de la Patagonia. 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 8880 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 918 records from Western Australia Museum, Crustacea Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1920-2004. 62099 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 2082 records from Vietnam Type Culture Collection. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 2848 records from Kangawalla Bird Sightings. 1 records from A new Garcorops species from Madagascar copal (Araneae: Selenopidae). 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 36 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust,. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Alcedinidae. 2297 records from Joint Nature Conservation Committee - England Otter Survey Database. 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 355 records from Culture Collection of Cryophilic Algae. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 3688 records from Clare Biological Records Centre dataset. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 18 records from First report of Dicopus longipes (Subba Rao) (Hymenoptera: Chalcidoidea) from India with new distribution data on some species. 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 12512 records from ULg_Hexapoda. 2880 records from Coleoptera, NEF. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 5872 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 33522 records from Dragonfly Ireland. 471 records from Aschelminth collection of National Museum of Nature and Science. 352507 records from BioFokus. 25813 records from Amphibian Specimens. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 4641 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 223433 records from Phytochorologie des départements français. 11 records from Pollen profile from sediment core AV14_K2-4. 4761 records from SMDB - Santa Maria Departamento de Biologia. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rynchopidae. 220546 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 27 records from RSPB - Bearded Tit National Survey in Britain 1992 (SCARABBS). 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 52 records from The Myrmica punctiventris and M. crassirugis species groups in the Nearctic region.. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 108 records from Studies in Hawaiian Diptera I: New Distributional Records for Endemic Asteia (Asteiidae). 374660 records from University of Florida Vertebrate Paleontology. 288571 records from Coordinated Waterbird Counts. 12051 records from ISM Ornithology Collection. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 4498 records from Colección Herbario Universidad Católica de Oriente. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 2 records from Note tassonomiche e faunistiche su Chilopodi della Grecia (Chilopoda). 767 records from BioGIS - Bats - Asaf Tsoar database. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 2802 records from Merseyside BioBank - North Merseyside Fish (unverified). 2 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 32 records from Archaea Collection in BCRC. 44567 records from DMNS Bird Collection (Arctos). 766 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 81329 records from natagora-earlybirds. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 2 records from Arthropoden aus südostalpinen Höhlen.. 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 9959 records from UAM Fish Collection (Arctos). 12434 records from Museu Paraense Emilio Goeldi - Coleoptera Collection. 723 records from The Fish Collection at the Zoologische Staatssammlung München. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 3 records from Melampyrum sylvaticum as a pre-diapause host plant of the scarce fritillary (Euphydryas maturna) in Finland. 255 records from GENT Lactarius Deliciosi. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 724 records from The Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 782 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 1 records from Zetes rubens. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 582 records from Bioblitz 2013 Copenhagen Denmark. 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 1 records from Nothrus pollinosus. 3945 records from TTRS Ornithology. 127876 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 9879 records from Bibliographic records of Angola mammals. 98423 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 72236 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 1 records from Myriopoden von Epirus. 102 records from Sipuncula collection of National Museum of Nature and Science. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1364 records from Irish Collembola records. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 207 records from BioAcoustica: Wildlife Sounds Database. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 7 records from First record of the male of the widespread Calliscelio elegans (Perkins) (Hymenoptera, Platygastridae) along with some taxonomic notes on the species. 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 13717 records from OUPR - Herbário "Professor José Badini". 21704 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 98 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1 records from Zetes ephippiatus. 514 records from SDSM Vertebrate Paleontology Collection. 588 records from Relative abundance of ostracods in sediment core Lz1120. 2654 records from Collection of Hymenoptera. 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 189 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Threskiornithidae. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 53071 records from CESJ - Herbário Leopoldo Krieger. 34237 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from Zetes fuscomaculatus. 22033 records from CUMV Mammal Collection (Arctos). 52 records from CIM Specimens. 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 496530 records from Field Museum of Natural History (Zoology) Bird Collection. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 4 records from Tunicata ZMK. 10 records from Cnidaria ZMK. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 513 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 1049 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 26624 records from Monitoring data from the federal state Bavaria (Germany). 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 1 records from Nothrus pigerrimus. 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 156 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 397 records from Danish Lacewings (Neuroptera). 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 3 records from Taxonomic considerations on Lobocneme Rehn, 1911 and Paroxyopsis Rehn, 1911 and a new synonymy (Insecta Mantodea: Stagmatopterinae). 7473 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 50 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 8 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 2358 records from MISE Project Otter Records, 2011-2015. 3377 records from USGS ASC - Changing Arctic Ecosystems - Alaska - Birds. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 15879 records from HAMAB - Herbário Amapaense. 820552 records from Fauna Atlas N.T.. 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 50 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 895 records from Lichen.ie Data. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 2143 records from The Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7208 records from Royal Horticultural Society - Records from the RHS insect reference collection. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 155 records from Megophthalmidia_of_North_America. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 99830 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 31000 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 1698 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 3 records from A revision of the Neotropical spider genus Ancylometes Bertkau (Araneae: Pisauridae). 21590 records from Butterflies of Ireland. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 8579 records from The atlas of breeding birds in Małopolska. 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 58 records from Mamíferos laguna El Tinije. 382 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Scolopacidae. 133656 records from NINA insect database. 1 records from Études myrmécologiques en 1886.. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 3904981 records from FlorKart - FlorenKartierung Gefaesspflanzen. 11731 records from HAS-Algae - Coleção Ficológica do HAS. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 873 records from Kartlegging av spredning av fremmede bartrær. 90868 records from CUMV Fish Collection (Arctos). 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 126307 records from UAM Mammal Collection (Arctos). 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 2444 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 47934 records from CRCM Vertebrate Collection. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 7410 records from Helgeland Museum, Lepidoptera. 710 records from Thames Valley Environmental Records Centre - Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 151 records from Molluscan fauna of Gueishan Island of Taiwan. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1952 records from ISM Ichthyology Collection. 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 260 records from SuLaMa reptile survey II 2012. 6065 records from LISU Herbario Angola. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 109 records from A taxonomic revision of the genus Oxyopomyrmex André, 1881 (Hymenoptera: Formicidae). 127226 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 6 records from MfN - Micropaleontology. 4 records from Beiträge zur Kenntnis der Spinnenfauna des Kt. Tessin III - Für die Schweiz neue und bemerkenswerte Spinnen (Arachnida: Araneae). 18940 records from Cowan Tetrapod Collection - Mammals. 38282 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 1905 records from BioGIS - Reptiles - INPA database. 2856 records from Alien macro-invertebrates in Flanders, Belgium. 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 2172 records from Colección de Reptiles. 2 records from Zobellia amurskyensis sp. nov., Zobellia laminariae sp. nov. and Zobellia russellii sp. nov., novel marine bacteria of the family Flavobacteriaceae. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 1652 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" (1989-1996). 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 76253 records from Irish Vascular Plant Data - Paul Green. 99 records from IWDG Ship Surveys Sightings - Heritage Council Surveys 2004. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 93276 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 1 records from A new African Apiocera species (Apioceridae, Diptera). 351176 records from Plantae of Costa Rica (INBio). 29490 records from Tromsø Museum, Fungi. 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 2481 records from HSU Wildlife Eggs and Nests. 301 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 13 records from Taxonomy of European Damaeidae (Acari: Oribatida) III. Species of the Kunstidamaeus tenuipes (Michael, 1885) group, with a description of Kunstidamaeus fraterculus n. sp. from East Slovakia. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 3 records from A new species of Lyssomanes Hentz, 1845 from Brazil (Araneae: Salticidae). 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 153 records from National Pine Marten Survey of Ireland 2005 - 2007. 8 records from A new pygmy grasshopper species (Tetrigidae: Tetriginae) from Central India. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 136 records from Plants galls. 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 948 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 3769 records from Eggs Specimen. 12109 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 92 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 464 records from Lepidoptera collection, NTNU, Trondheim. 13325 records from Herbier du Bénin. 9123 records from Flora of Słowiński National Park, Poland. 711 records from Odonata collection, NTNU, Trondheim. 3947 records from The importance of host tree age, size and growth rate as determinants of epiphytic lichen diversity in boreal spruce forest.. 2983 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 19 records from Counts of benthos communities in Kongsfjorden in 2009. 1948 records from CCBER Mammalogy Collection. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 9 records from Cypridinid Ostracods. 20 records from Inventario Herpetológico EPF Floreña, Yopal, Casanare. 41630940 records from Artdata. 1826 records from Collection des Mollusques (BOUM). 2577 records from Shellfish (WSHN-MS). 90 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 77244 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 519292 records from Museum Victoria provider for OZCAM. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 540 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 1 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 78915 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 1322 records from PSUZC-Amphibians Collection. 1 records from Nothrus canaliculatus. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 63 records from Revision of the ant genus Myrmoteras in the Malay Archipelago (Hymenoptera, Formicidae).. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 8243 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 4 records from New genus of diminutive microhylid frogs from Papua New Guinea. 3 records from Diatom abundance of Hole 38-338, Part 2. 71 records from (Data S1) Palynology of ODP Site 113-696. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 13995 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 6 records from Arthropoden aus südostalpinen Höhlen. 314 records from Peces laguna El Tinije. 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 777 records from INRA-Versailles Arabidopsis natural variants. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 91 records from European bison in Białowieża Primary Forest. 2904 records from Harvestmen_of_French_Guiana. 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 2815 records from Helgeland Museum, Araneae. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 9792 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 24 records from Description of the males of Euprosthenops australis Simon, 1898 and Euprosthenopsis pulchella (Pocock, 1902) (Araneae: Pisauridae). 665 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Brown Hare Survey. 527 records from Inventaire floristique de Beza Mahafaly. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 3 records from New Species of Woolly Lemur Avahi (Primates: Lemuriformes) in Bemaraha (Central Western Madagascar). 2 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 1803 records from Flora of tanzania. 10 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 16195 records from People's Trust for Endangered Species - Hedgehog records 2005-2006: Hogwatch and Rural Landowner surveys. 276513 records from MBM - Herbário do Museu Botânico Municipal. 51748 records from Museu Paraense Emilio Goeldi - ichthyology Collection. 13625 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 2412 records from Ohio University Invertebrate Paleontology Collection. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1323 records from Algae (KBRC-AG). 4998 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 1664 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 23 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 1023 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 132 records from Fiocruz/CCAMP - Coleção de Campylobacter. 30129 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 3382 records from People's Trust for Endangered Species - Hedgehog Hibernation Survey records. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 11762 records from Chrysomelidae of the Carpathians. 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 1 records from On the Chilopoda from Turkey. 882456 records from SA Fauna (BDBSA). 10255 records from Araneae Collection. 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 3720 records from Saproxylic Beetles of Ireland. 2 records from Description of Hoplolaimus bachlongviensis sp. n. (Nematoda: Hoplolaimidae) from banana soil in Vietnam. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 1 records from Hesperinus ninae Papp & Krivosheina (Diptera: Hesperinidae) from Georgia: the second record of this peculiar species. 12 records from Echinodermata ZMK. 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 2868 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 3276487 records from Insecta of Costa Rica (INBio). 62015 records from Atlas of Iberian water beetles (ESACIB database). 11392 records from Danish Plant Bugs (Miridae). 1 records from SDSM Botany and Paleobotany Collections. 55056 records from Biological Records Centre - Reptiles and Amphibians Dataset. 15953 records from Algae (S). 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 18 records from Survey of the native freshwater opossum shrimp (Mysis relicta) in Ireland. 2506 records from Museu Paraense Emilio Goeldi - Opiliones Collection. 3 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 906 records from Digital Florula - Las Cruces Biological Station. 24121 records from Endemic plants of the Congo basin. 3 records from Collection Crustacea - ZSRO. 2217 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 119 records from Various insect orders, NEF. 1 records from Celaeno spinosa. 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 584476 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 16452 records from Fungus herbarium, UiB. 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 2957 records from HSU Wildlife Mammals. 411 records from SuLaMa reptile survey I 2012. 147466 records from AIMS, Long-Term Fish Visual Census, Great Barrier Reef, Northeast Australia, 1992-2015. 72185 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 657 records from MVZ Hildebrand Collection (Arctos). 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 159024 records from Lund Museum of Zoology (MZLU). 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 223522 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 12876 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 6 records from Vermes ZMK. 111682 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Protozoa ZMK. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 1 records from Ctenophora ZMK. 382 records from Reptilia ZMK. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 3 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 19 records from The first case of aggressive mimicry among lamprologines in a new species of Lepidiolamprologus (Perciformes: Cichlidae) from Lake Tanganyika.. 37694 records from Tallinn Botanic Garden. 200 records from Zoological collection of the National Museum. 2777 records from Plant (KIWE-PL). 11961 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 146809 records from OHN. 30 records from Specimens from India at the University Museum at the University of Bergen. 192273 records from Field Museum of Natural History (Zoology) Mammal Collection. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 1129 records from Upper Silesian Museum, Insect Collection. 370 records from Ichthyologie ZMK. 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 51 records from Packer Collection / Xenochilicola bees, Chile. 1626 records from Ornithologie ZMK. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 439 records from Museu Paraense Emilio Goeldi - Scorpiones Collection. 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 2 records from Amphibia ZMK. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 591211 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 1 records from Oribates angulatus. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from Nothrus bispinosus. 5 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 496203 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 39 records from Arachnologie ZMK. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 27290 records from Bird Monitoring Data. 165299 records from CAS Invertebrate Zoology (IZ). 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 281 records from Myriapoda of Costa Rica (INBio). 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 637399 records from Données ONF Faune-Flore-Fonge. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 16621 records from Crustacea collection of National Museum of Nature and Science. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 28 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 3221 records from Road Kill Survey. 1 records from Nothrus bicarinatus. 2 records from Bryozoa ZMK. 20991 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 5856 records from FCAB - Herbário Friburguense. 1262 records from Crustacea ZMK. 104 records from Mammalogie ZMK. 32109 records from Herbier de Nouvelle-Calédonie. 2 records from Pantopoda SMF. 68 records from Malakologie ZMK. 6551 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 2 records from Porifera ZMK. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 1 records from On centipedes (Chilopoda) of Albania, 2. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 1 records from On the Chilopoda from Turkey. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 61 records from Shrews of Poland. 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 15925 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 1029 records from Freshwater plants of Cameroon. 4 records from New country records of reptiles from Laos. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 2224 records from UCM Bird Eggs/Nests Collection (Arctos). 11251 records from Herbarium areqvipense (HUSA). 21091 records from NCSM Birds Collection. 5581 records from IWDG Casual Cetacean Sightings. 144 records from Checklist of Fabaceae Lindley in Balaghat Ranges of Maharashtra, India. 19700 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 30926 records from Annelida collection of National Museum of Nature and Science. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 110 records from Birdrace-LiLaMai-Vechta. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 285 records from Sylva Foundation - European Pear Rust (Gymnosporangium sabinae) monitoring. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 5318695 records from Australia's Virtual Herbarium. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 4852552 records from Bird Ringing Centre in Sweden (NRM). 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 3 records from Mammals (SMNH-MM). 1 records from Hypochthonius rufulus. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 14420 records from Colección Nacional de Foraminíferos - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 1942 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 1000 records from Colección Limnológica del Chocó. 108 records from Birdrace-TriumVIErat-Viersen. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 1614 records from Culture Collection of Algae. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 1 records from Die Chilopodenfauna Griechenlands. 23 records from Description of Cathorops manglarensis, a new species from the Colombian Pacific, with redescription of Cathorops multiradiatus (Siluriformes; Ariidae).. 1 records from Amycolatopsis marina sp. nov., an actinomycete isolated from an ocean sediment. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 89 records from Collection Crustacea - PUM. 1 records from Nothrus convexus. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 2223 records from Colección de Zoología Invertebrados - Otros invertebrados. 9 records from Chenopodium vulvaria. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 385 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Laridae. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 15 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 210019 records from Invert Paleo Specimens. 688 records from Algae, Norwegian College of Fishery Science. 2095 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 1641 records from NCSM PaleoBotany Collection. 749213 records from Historical Bird Atlas. 1329 records from Colección de Invertebrados Cenpat (CNP-INV). 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 28735 records from UAM Bird Collection (Arctos). 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 2666 records from Insect (JNHM-IN). 2 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 2 records from A redescription of Lophostica mauriciana Simon, 1902 (Araneae: Salticidae). 12542 records from Herbarium of the Université Libre de Bruxelles. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 163 records from A review of Lamyra Loew (Diptera: Asilidae: Laphriinae). 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 67 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 9933 records from CHAS Mammalogy Collection (Arctos). 9 records from Corumbataia britskii (Siluriformes: Loricariidae: Hypoptopomatinae) a new species from the upper Rio Parana basin, Mato Grosso do Sul, Central Brazil.. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring. 1415 records from Plant observations from Białowieża National Park. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 377 records from Herbario MAIA, colección de Eucaliptus del INIA-CIFOR. 16568 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 1055244 records from Norwegian Biodiversity Information Centre - Other datasets. 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 34 records from Caddisfly Records, Edenvale, Co. Wexford 2010. 29513 records from MPM Herpetology. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2502 records from ISM Herpetology Collection. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 337 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 724 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 57401 records from Naturalis Biodiversity Center (NL) - Mammalia. 7551636 records from BirdLife Australia, Birdata. 3117 records from Naturalis National Natural History Museum (NL) – Coelenterata. 58044 records from Naturalis Biodiversity Center (NL) - Cnidaria. 60 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 15 records from Chenopodium. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 8 records from Torpedo formosa sp. nov., a new species of electric ray (Chondrichthyes: Torpediniformes: Torpedinidae) from Taiwan.. 7000 records from CCBER Ornithology Collection. 2954 records from Geneva Herbarium – Burnat Herbarium (G-BU). 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 7 records from (Table 4) New palynological record of sediments from Odderade. 21694 records from arim. 6812 records from Invertebrate collection of University of Oulu Zoological Museum. 8887 records from The tunicates collection (IT) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5658 records from ESAS cetacean sightings from 1980 to 2003.. 8102 records from tef-database. 6821 records from Staatliches Naturhistorisches Museum Braunschweig - Coleoptera Collection. 2 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 299492 records from SEAPOP NINA. 589 records from Birds (NMNO-BI). 36048 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 2064712 records from Museum of Comparative Zoology, Harvard University. 2625 records from (Table 1) Stratigraphic distribution of planktonic foraminifera from the uppermost Miocene to upper Pliocene in ODP Hole 134-832B. 48 records from Tardigrada collection of National Museum of Nature and Science. 718 records from HSU Vertebrate Museum Amphibian Collection. 432 records from Plantas Bosque Seco Chicamocha. 9948 records from Bees of Canada / Gschwendtner property collection. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 56302 records from Kathryn Kalmbach Herbarium. 1 records from Nothrus palliatus. 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 1667138 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 16 records from Moenkhausia pankilopteryx, new species from rio Tocantins drainage, Brazil (Ostariophysi: Characiformes, Characidae).. 13503 records from Collection of various insect orders, Natural History Museum, University of Oslo. 450 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 38841 records from Herbier de Strasbourg. 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 1 records from Flora of Suriname, volume VI, part I. 1288 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 197454 records from Vascular Plant Herbarium, UiB. 17 records from Hazel Dormouse in Ireland. 6211 records from NMMNH Mammal. 1696 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 27033 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 637 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 1808 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 55 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 197054 records from Ichthyology Collection - Royal Ontario Museum. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 163 records from Entomofauna laguna El Tinije. 260950 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 74 records from SuLaMa reptile monitoring. 1833 records from Censos navideños de aves y censo neotropical de aves acuáticas en 10 áreas protegidas de Parques Nacionales Naturales de Colombia.. 2087 records from Banco de Germoplasma del Jardín Botánico Atlántico. 1299 records from Waarneming.nl (NL) - Great Grey Shrike Count 2014-2015. 120208 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 200913 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 98234 records from CAS Ornithology (ORN). 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 1910784 records from Consortium of California Herbaria. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 192907 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 169 records from The Pteridaceae family diversity in Togo. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 22 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 6004 records from Colección Limnológica Universidad de Antioquia. 29171 records from Naturalis Biodiversity Center (NL) - Collembola. 1458 records from Waarneming.nl (NL) - Great Grey Shrike Count 2013-2014. 8026 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 5790 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 1965 records from Global caridean shrimp fauna. 1077 records from BioGIS - Fish - HUJ collections. 418 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 50000 records from observe_tuna_bycatch_ecoscope. 10866 records from Heteroptera of Ireland. 480 records from Spiders_of_French_Guiana. 71 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 21868 records from Fishes in MZNA-VERT: foraging ecology of the kingfisher. PhD project, Antonio Vilches. 798 records from Biological Records Centre - Irish Otter Dataset. 98 records from Colección Nacional de Heliconias. 70111 records from Kyushu University Museum Coleoptera Collection. 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 18900 records from UCBG TAPIR Provider. 21 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 1733 records from Birds collection of Abiko City Museum of Birds. 30000 records from Birds collection of Yamashina Institute for Ornithology. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 6884 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 164 records from EcoRecord - Flatworm Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 20957 records from CHAS Herpetology. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 823 records from Líquens d'Andorra. 1 records from Zetes morticinus. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 22167 records from Natural History Museum Maastricht (NL) - Herbarium. 164 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 7 records from Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae).. 16696 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 1 records from Zetes latipes. 6 records from Mammalia (JNHM-MM). 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 3002 records from Colección de Peces Universidad Católica de Oriente. 951235 records from iNaturalist Research-grade Observations. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 807 records from Reunion_Coffea. 211883652 records from EOD - eBird Observation Dataset. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 6 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 50128 records from Tasmanian Museum and Art Gallery provider for OZCAM. 69622 records from Fundación Miguel Lillo - Colección Entomológica. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 49637 records from Monitoring data from the federal state Hesse (Germany). 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 175 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 25543 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 9787 records from Finnish Entomological Database: Hymenoptera. 8629 records from National Taiwan University. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 1 records from Oribates ovatus. 3225 records from Aquatic Oligochaeta of Ireland. 172126 records from CONN. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 113112 records from Recent Invertebrates Specimens. 5578 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 2 records from Neue Milbenarten aus Kärnten. 14760 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 73 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 323085 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 27 records from New records of Sylvicola (Diptera: Anisopodidae) from Romania. 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 2 records from A new species of Neossos Malloch (Diptera: Heleomyzidae) from the Yukon Territory, Canada, and a revised key to the Nearctic species. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 3669 records from ARKO strandeng. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 2 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 43 records from A Unique Nest-Protection Strategy in a New Species of Spider Wasp. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 1 records from Hoplophora crinita. 40481 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 558827 records from Aranzadi Ringing Scheme (bird ring-recovery data). 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 47871 records from H.A. Stephens Herbarium. 4 records from A new ant genus from the southwestern United States.. 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 13968 records from NYSM Birds. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 352 records from Universidad de Málaga: MGC-Lichen. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 30009 records from HUCS - Herbário da Universidade de Caxias do Sul. 34 records from National System of Protected Areas in Poland - Fungi. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 154 records from UCM Vertebrate Observations Collection (Arctos). 102 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 16 records from Mollusca Colelction of the Seto Marine Biological Laboratory, Kyoto University. 8518 records from Upper Silesian Museum, Bird Observations. 1896 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 22 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 70432 records from National Bat Database of Ireland. 1594 records from Musée Vert ornithology collection. 21749 records from University of Lethbridge Herbarium (LEA). 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 181 records from Alien Species in Poland - Animals. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 86659 records from UCT: Southern African Butterfly Conservation Assessment (1815-2009). 131642 records from mel. 1 records from Nothrus piceus. 1369 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 319 records from HTSAw - Xiloteca do Trópico Semiárido. 2115 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 38 records from Inventario de Murciélagos Buena Vista, Jaramá, Yopal, Casanare. 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 2275 records from UFRN-Fungos - Herbário UFRN - Fungos. 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 150 records from Birdrace-Ostseevögel-Ostvorpommern. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 23046 records from Hemipteran specimens of Iwate Prefectural Museum. 2043 records from Mollusca Collection of Natural History Museum and Institute, Chiba. 1000 records from Mollusca Specimens of Oiso Municipal Museum. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 9399 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 69 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 324 records from People's Trust for Endangered Species - Noble Chafer: Post-BAP records from 1998 onwards. 11 records from A new rainbowfish (Teleostei: Melanotaenioidei: Bedotiidae) from the southeastern highlands of Madagascar, with comments on the biogeography of Bedotia.. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 3 records from Salticidae from the Himalayas. The genus Hasarius Simon, 1871 (Araneae: Salticidae). 4829 records from Coleção de Polychaeta do Museu Nacional. 164 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 29 records from A Revision of the Genus Synagelides Strand, 1906 (Araneae, Salticidae) in Korea. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 6774 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 3 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cinclidae. 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 1 records from Murcia trimaculata. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 86893 records from ALCB - Herbário Alexandre Leal Costa. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 15813 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 4498 records from Flora of Japan Specimen Database. 86 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 10339 records from KUBI Ichthyology Tissue Collection. 1900 records from Fungi Collection. 110017 records from Louisiana State University Herbarium - Vascular Plants. 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 13909 records from AM: Terrestrial Insect Collections (1896-2000). 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 33173 records from Global Lacustrine Diatoms. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 1752 records from Herbier National de Mauritanie (HNM). 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 129 records from Mammalia (KNAM-MM). 212157 records from Estonian Museum of Natural History. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 11 records from Pollen profile from sediment core AV14_K2-1. 1035 records from National Museum Of Marine Science & Technology. 998 records from minsok. 178 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 238 records from John Muir Trust - List of Lichen Species recorded on high ground in the Ben Nevis range. 850 records from Shellfish (NHMK-MS). 417355 records from University of California Museum of Paleontology. 617 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 4745 records from Collection botanique Le Grand A. (BOUM). 15973 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 98 records from acari. 2966 records from Bolivian Amazon lowland fish metacommunity data. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 10000 records from Coleccion Entomologica CEI - CCT Mendoza CONICET.. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 348808 records from Estonian University of Life Sciences. 1266 records from Actinomycetes Collection in BCRC. 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 6 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 64 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827B. 1914 records from Macrophytes_CLF. 1244 records from Mosquitoes_of_French_Guiana. 23215 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 923 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 114 records from Birdrace-Finkenspötter-München. 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 8706 records from NINA botanical collection. 258 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 1359 records from CSIRO, Cruise SS199701, Marine Biological Survey, South Tasmania, Southeast Australia, 1997. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 1 records from Zur Kenntnis der Lithobiiden. 43857 records from Mammals housed at MHNG, Geneva. 392968 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 7 records from Kryptolebias sepia n. sp. (Actinopterygii: Cyprinodontiformes: Rivulidae), a new killifish from the Tapanahony River drainage in southeast Surinam.. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 419514 records from Meadow and Pasture Inventory (SJV). 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 7046 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 1031 records from Circumpolar Seabird Monitoring Plan. 14067 records from DMNS Marine Invertebrate Collection (Arctos). 84521 records from BioGIS - Vascular plants - INPA database. 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 19553 records from Wildbook for Whale Sharks. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 1447 records from Odonata of the Congo River 2010 expedition. 79406 records from KUBI Vertebrate Paleontology Collection. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 56 records from Onychophora of Costa Rica (INBio). 5928 records from HUSC - Herbário Unisanta. 25128 records from rmca-albertine-rift-butterflies. 8793 records from HPBR - Herbário Padre Balduino Rambo. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 544 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 1489 records from Herbarium Rhoenmuseum Fladungen. 8441 records from Natural England - Batsites inventory for England. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from A new genus and species of Acaenitini (Hymenoptera, Ichneumonidae, Acaenitinae) from China. 23 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 1 records from Campylomorphus homalisinus (Elateridae): a new species for Lombardy (Italy), with notes on its ecology, distribution and biogeography. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 204947 records from CAS Ichthyology (ICH). 221721 records from Essig Museum of Entomology. 5254 records from The Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 42517 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 18004 records from Census of the animals of Benin. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 10234 records from Collection entomologique Barthélémy. 11 records from Himantura hortlei n. sp., a new species of whipray (Myliobatiformes: Dasyatidae) from Irian Jaya, Indonesia.. 39 records from ECOCEAN MantaMatcher. 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 20 records from Cyatta abscondita: Taxonomy, Evolution, and Natural History of a New Fungus-Farming Ant Genus from Brazil. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 613 records from Countryside Council for Wales - Shad Monitoring data. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 9 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 959 records from SMNS Palaeontological collection - Fossil mammals. 25883 records from Monitoring data from the federal state Saxony (Germany). 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 1 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 1 records from On the Chilopoda from Turkey. 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 22031 records from Fishes in MZNA-VERT: baseline freshwater sampling campaigns. 10 records from Redescription of the little-known grasshopper Willemsella (Acrididae, Hemiacridinae) from Peninsular Malaysia. 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 987 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thraupidae. 6475302 records from NMNH occurrence DwC-A. 61468 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 69 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 10 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 3327 records from BioGIS - Mammals - SPNI. 15686 records from DMNS Mammal Collection (Arctos). 39766 records from BioGIS - Vascular plants - A. Danin's point database. 1 records from Nothrus mutilus. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 360 records from Order Araneae. 15927 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 8052 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 1189 records from kerkyra. 1166 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 29264 records from NCSM Vertebrate Paleontology Collection. 205 records from infish. 1353 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 5549 records from Diplopoda (NSMK-DI). 1659 records from MISE Project Waterford Otter Records, 2011-2015. 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 4 records from Pollen analysis of sediment profile WO1 from Wollingster See. 17447 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 33 records from (Table 2) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585A. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 50805 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 55 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 37 records from Berlin - Treptower Park / Karpfenteich. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 56 records from Zitadelle Berlin-Spandau (7b). 219 records from Umgebung der Grundschule Oderberg. 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 142 records from Kinderbauernhof Pinke-Panke. 1915 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 72 records from Birdrace-Buteo2DO-Dortmund. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 80 records from Förderzentrum Schmölln. 151 records from Isarufer. 44 records from "Schlechteberg" Ebersbach/Sa.. 245 records from Kiesgruben Wemb. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 64 records from Kabelskebach (Kabelsketal, Saalkreis). 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 46 records from Hainbachtal in Oelsnitz/V.. 180 records from Paul-Gerhardt-Schule Dassel. 183 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 5450 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 57495 records from TNHC Ichthyology Collection. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 128787 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 638 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 128 records from Birdrace-Brut-Wetteraukreis. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 109 records from Birdrace-Team_Charadrius-Günzburg. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 100 records from Birdrace-Meister_der_Herzen-Kleve. 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 252060 records from Moths Ireland. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 523 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ardeidae. 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 100 records from PSUZC-Reptile Collection. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 120 records from Birdrace-Kosmos_Racer-Freising. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 101 records from Birdrace-Herford-Birder-Herford. 2413 records from Literature based species occurrence data of birds of North-East India. 112 records from Birdrace_Die_Borner-Viersen. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 105 records from Birdrace-ARKONAuten-Rügen. 95 records from Birdrace-Buteo1_DO-Dortmund. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 127 records from Birdrace_Schräge_Vögel-Herford. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 113 records from Hochschulgelände (Bremen). 57 records from Heidesee / Halle. 5036 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 101 records from Naturgrundstück (Eutin). 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 270 records from Regenrückhaltebecken (Zeulenroda). 313 records from Stadtpark Herzberg (Elster). 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 167 records from Zielbach (Töll). 39 records from Südpark (Bochum-Wattenscheid). 36138 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 32 records from Schulhof Sandhofenschule (Mannheim). 163 records from Brander Wald (Stolberg). 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 91 records from Birdrace-Enger_am_Spektiv-Herford. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 360 records from Küstenschutzwald. 198 records from FNL e.V.. 271 records from Beweidungsprojekt an der Nesse. 100 records from Feriendorf Ober-Seemen. 105 records from Feriendorf des Kreises Gedern (Ober-Seemen). 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 97 records from Döchtbühlwald (Bad Waldsee). 84 records from Roter Berg Werdau (Leubnitz). 57 records from Waldhusener Moor (Lübeck-Kücknitz). 233 records from Föhrenried (Fronreute und Baindt). 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 96 records from Birdrace-federleser-Herford. 92 records from Birdrace-Team_BO-bachter-Bochum. 85 records from Birdrace-Die_Paradiesvögel-Herford. 103 records from Birdrace-Die_Nachtigallen-Herford. 88 records from Birdrace-WeserEggeLäufer-Höxter. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 59 records from Im Bauerngarten. 33 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from RV Poseidon cruise 334. 2813 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 241 records from BIRDRACE RennVögel Münsterland. 34 records from Borkhart. 2 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 83 records from Spechtwald. 97 records from LauWi. 100 records from Grenzturm Hohen Neuendorf. 70 records from Lech 2001. 52 records from Fledermaus. 69 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 69 records from Lassentiner Moor (Niepars). 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 102 records from Birdrace-Die_Nachtraben-Stuttgart. 76 records from Birdrace-Birding_for_Nature-Bonn. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 137 records from VFD-H: Rheingau: Pferdeweide Loock. 185 records from Klasse 3a. 257 records from Seewasen. 162 records from Siegen/ Gymnasium Am Löhrtor. 342 records from Kremmer Luch. 114 records from Flora. 122 records from Kloster Eberbach. 144 records from Ehmkendorf. 55 records from Waldsee. 87 records from Biotop "Kohlbeke" (Berlin-Marzahn). 103 records from Fuchsloch (Mohlsdorf/Ostthüringen). 263 records from Artenvielfalt Kreis Gießen. 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 282 records from Deponie Klausdorf. 23 records from Alter Nördlicher Friedhof (München). 69 records from Schulgarten mit Klasse 8a (Essen). 15 records from AKG-Bensheim. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 20 records from Motzener Tonsee. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 170 records from Bodenseeufer Radolfzell. 158 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 325 records from Triebesbach (Zeulenroda-Triebes). 22 records from Dellwiger Bach (Dortmund). 69 records from "Schwarzes Teich" (Waldpark Radebeul). 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 308 records from Wangerooge. 101 records from Naturhausgarten. 64760 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 248 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 45 records from Flusswerder in der Weser (Hameln). 150 records from Steinbruch Mainz-Weisenau. 54 records from Wiese am Unterbecken. 95 records from Ortelsbruch - Hangmoor bei Morbach. 41 records from Örtzemündung (Stedden). 10 records from Kita-Wäldchen Fuchsturmweg Jena. 96 records from Die Wuhle. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 149 records from Wirbach. 145 records from privater Garten. 86 records from Alter Kreidebruch Saßnitz/Rügen. 31 records from Nationalpark Harz Schul-AG Braunlage. 122 records from Stever. 12 records from Kindergarten. 117 records from Wassermann. 9 records from Willersalpe. 66 records from Wedeler Au. 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 264 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 113 records from Rund um das LUGY. 304 records from Ried und Sand - Artenvielfalt durch Beweidung. 50 records from Junge Heide, Radebeul/Dresden. 106 records from Schulgarten Hans-Carossa-Oberschule. 107 records from Landschaftsschutzgebiet Buchhorst 3. 54 records from Zentralfriedhof (Wien). 108 records from Mainufer. 79 records from Balkon (Norderstedt). 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 1037 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 65 records from Mauernacker (Wettsaasen). 5 records from Streuobstwiese (Mittelgasse 4). 17 records from Schutzgebiet Ochtersum. 253 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 161 records from Schussenaue bei Berg. 85 records from Insektenvielfalt Ahe/Weichelsee. 54 records from Ludwigshofen. 18 records from Spielwiese. 73 records from Varnhalt. 59 records from Rund ums Ökohaus (Würzburg). 181 records from Spießwoogtal / Königsbruch (Fischbach). 103 records from Schwanseepark (87645 Schwangau). 35 records from Urwald 3 (Bad Waldsee). 4 records from Arthropoden aus südostalpinen Höhlen.. 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 99 records from Dorfrand Mauderode. 110 records from Obstwiese Osterberg. 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 79 records from GymnQuerfurt. 63 records from Erft in Selikum (Neuss). 18 records from Mittelstreifen. 99 records from Düne am Ulvenberg (Darmstadt). 1 records from Papilio Sticheli nov. spec. aut subsp.. 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 111 records from Ökologischer Weinberg (Guntersblum). 160 records from Wirbach-Taubental (Bad Blankenburg). 48 records from Trockenrasen bei Dörndorf. 77 records from Trockenrasen Franzigmark (Halle/Saale). 41 records from Wiese und Bach beim Unterbecken (Markersbach). 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 22 records from Heilpflanzen im Hainbachtal. 22 records from Kaltenkirchen Brache. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 124 records from Wiesenbiotop am Wasserturm. 103 records from Wasserwerkspark (Chemnitz). 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 30 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 55 records from Flora und Fauna am Mittelrheintal. 95 records from Vielfalt verschiedener Wiesen. 110 records from Birdrace-Alle_Vögel_sind_schon_DADA-Uckermark. 172 records from Leben im Finkensteiner Moor. 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 100 records from Birdrace-The_Ringers-Friesland. 23 records from Wiese Niederaula. 212 records from Artenvielfalt im Beckerbruch (Dessau). 28 records from Sandgrube Zaisertshofen. 11 records from Desarrollar las actividades tendientes al manejo, conocimiento y conservación del Comino crespo (Aniba perutilis hemsl.), formuladas en el plan de conservación para la especie en el departamento del Meta. 171 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 59 records from Oschenberg, NO von Bayreuth-Laineck. 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 28 records from Hainbachtal bei Oelsnitz / V.. 94 records from Kochertgraben II. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 22 records from Breitkopfbecken (Berlin-Reinickendorf). 58 records from Weidewirtschaft. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 47 records from Neanderthal. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 96 records from Birdrace-Berlin_Sparrows-Uckermark. 113 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 16 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 63 records from Sternwiese Mülheim-Broich. 5 records from Feuchtwiese. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 50 records from Artensuche auf den Elbwiesen in Radebeul. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 98 records from Warnowtal (Rostock). 245 records from Gieselbachtal Fulda-Harmerz. 43 records from Saalewiesen Naumburg. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 244 records from WildesMoor bei Schwabstedt. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 147 records from NABU-Auerochsenweide. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 297 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 28 records from Uferzone Wipper (Biesenrode). 139 records from NSG Leist bei Ziegenhain. 62 records from Amtsrain Apolda-Zottelstedt. 61 records from Artenvielfalt auf der Wiese. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 43 records from Schulgelände Thurmair-Gymnasium. 881 records from Moluscos Marinhos de Augusto Nobre. 16505 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 4 records from Schulbiotop und Brigach (Villingen). 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 19 records from Goethe-Hauptschule/Projekt I-10. 153 records from Selztal bei Friesenheim. 51 records from Revision of the Nearctic endemic Formica pallidefulva group.. 40 records from Flächennaturdenkmal Grubditz. 60 records from Schafsweide Seniorenhaus Berghof. 53 records from Weidegut Rechab. 214 records from Binsenwiesen. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 155 records from Bammentaler Duft- und Heilkräutergarten. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 101 records from Isartal Dingolfing. 92 records from Birkenloh. 172 records from Dalbekschlucht. 93 records from Höltigbaum. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 80 records from VFD-RP: Taunus: Ponykoppel Thurner. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 63 records from Hochschule Zittau/Görlitz. 98 records from Rund ums Cani. 107 records from vegoek. 207 records from Biosphäre Bliesgau. 355 records from Carábidos (Coleoptera: Carabidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 134 records from Birdrace-Team_Havelland-Havelland. 9871 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 133 records from Wulfsmuehle/Pinnau. 87 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 97 records from Landschaftspark St.Leonhard-Deisendorf. 122 records from Birdrace-Hügelland-Mainz/Bingen. 81 records from Stadtpark Schmölln. 16 records from A review of the systematics of western North Pacific angel sharks, genus Squatina, with redescriptions of Squatina formosa, S. japonica, and S. nebulosa (Chondrichthyes: Squatiniformes, Squatinidae).. 61 records from GE-Brühl. 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 193 records from Gelände des Schulzentrums am Himmelsbarg. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 169 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 89 records from Birdrace-Team_Wangerooge-Friesland. 53 records from Bad Bodenteicher Heide. 86 records from Naturerlebnisraum Koppelsberg (Plön). 15 records from Regenwasserabfangsbecken (Erlenbach). 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 46 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 69 records from Entdeckertour am Muldestausee 1/05. 54 records from Weidegebiete in der Selzrenaturierung. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 39 records from Soolbach-Tal. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 79 records from Birdrace-Bielefinken-Bielefeld. 102 records from Industriebrache (Kempen). 257 records from Dinocyst occurrences and zonations from IODP Hole 313-M0028A. 60 records from NABUGEO1. 10 records from Feuchtwiesen Wippertal bei Wippra. 40 records from Öhmdwiesen und Göldern (Konstanz). 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 155 records from Birdrace-Usedommeln-Ostvorpommern. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 128 records from Birdrace_turbine_untersee-Konstanz. 2916 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 62 records from Zoo Frankfurt. 36 records from Selz (Ingelheim am Rhein). 65 records from LSG "Großes Bruch". 51 records from Steinbachtal (Würzburg). 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 57 records from Garten in Schmölln. 49 records from Dörnberg. 39 records from Regenrückhaltebecken Bad Bevensen. 15 records from Die geheimnisvolle Welt der Spinnen. 27 records from Vögel. 15 records from Naturschutzgebiet Ahrschleife (Altenahr). 11 records from Waldgebiet Todtnau- Sonnhalde. 57 records from Mauervegetation,Flechten und anderes. 23 records from Schulgarten der Hainbuchenschule (Hagenbach). 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 42 records from sbosch. 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 31 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 1346 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 221 records from Römertal (Steinpleis). 21 records from Riedkanal Bötzingen. 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 12 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 48 records from Morphologische Daten von Natrix. 21 records from Bach. 29 records from Naturerfahrung. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 64 records from Schafheide im Böblinger Wald. 45 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 101 records from Hoher Stein Kallenhardt. 51 records from Mühlenbach bei Buxtehude. 70 records from Birds (SMNH-BI). 81 records from Schulgarten-St.-Georg-Gymnasium. 13 records from Garten Hamburg Uhlenhorst. 31 records from Kurler Busch (Scharnhorst). 57 records from Schulgarten Fichteschule. 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 39 records from Stausee Weiditz. 46 records from 8c. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 81 records from Birdrace-Die_Ornithomaten-Herford. 78 records from Birdrace-Die_Laufenten-Braunschweig. 54 records from Park Schönfeld (Kassel). 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 47 records from Schulgelände Ceciliengymnasium. 21 records from Tauchen und Meer 02. 35 records from Gym Freyung. 47706 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 71 records from Birdrace-do_elster_Dortmund. 87 records from Klütwald. 31 records from Regenwasserabfangbecken. 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 10 records from Ökowerk Emden. 84 records from Streuobstwiese Haus Zeitz. 13 records from Tiere im Teichgebiet. 64 records from Issumer Fleuth. 23 records from Ackerrain Plönhagen. 24 records from Ornithologische Wanderung um Tussenhausen. 1 records from Hoplophora ardua. 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 23 records from Tümpel Schulbiologiezentrum. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 13 records from FND "Weißer Berg" Leißling. 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 59 records from Schulteich Freie Waldorfschule Darmstadt. 1 records from Waldtag in und um Seelingstädt. 74 records from Schulwald Grundschule Brügge. 47 records from Revised diagnosis of the genus Bangana Hamilton, 1822 (Pisces: Cyprinidae), with taxonomic and nomenclatural notes on the Chinese species.. 40 records from Schulhof Liebfrauenschule Oldenburg. 36 records from Plöwener Wald. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 4483 records from MVZ Bird Observations (Arctos). 117 records from Naturschutzgebiet Kochertgraben. 26 records from Erhard Sopp. 22 records from Bachabschnitt der Nette (Osnabrück). 32 records from Nationalpark Harz Juniorranger. 15 records from Beisetal bei Niederbeisheim. 51 records from Schrebergarten Düsseldorf Oberkassel. 64 records from Pilzlehrwald. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 56 records from Estetal (Buxtehude). 23 records from AKG-Gelände in Bensheim. 28 records from Stadtpark Prinzengarten (Sigmaringen). 4 records from Weser und Weseraue bei Höxter, Godelheim und Boffzen. 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 11 records from Privatteich(St.Leon). 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 37014 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 141 records from Draubiotop Lavamünd. 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 27 records from Zwickau- Schwanenteich. 1174 records from Sudeniederung (Amt Neuhaus). 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 29 records from Brenz (Heidenheim). 19 records from Glemstal (Leonberg). 14 records from Three new species of the seasonal killifish genus Simpsonichthys, subgenus Hypsolebias (Teleostei: Cyprinodontiformes: Rivulidae) from the rio Paracatu drainage, rio São Francisco basin, Brazil.. 36 records from Olympiapark (München). 20 records from Lerchenauer Baggersee (München). 80 records from Lahnufer in Villmar. 24 records from Kaisertal. 48 records from Heider Bergsee (Brühl). 11 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 20 records from Mikroorganismen. 12 records from Kinderwald Hannover. 18 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 36 records from Salzwiese Diekskiel. 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 3 records from FFR Hausen. 9 records from Wiesendreieck Luckenwalde. 26 records from Schulteich Heinrich-Mann-Schule. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 68 records from Streuobstwiese. 10 records from schlittschuhweiher. 27 records from Wiese hinter der Schule (Darmstadt). 8 records from Kleiner Ziergarten Winzingen (Neustadt). 29 records from Insekten. 719 records from IBF Monitoring of Plant Galls. 6 records from Fließgewässeruntersuchung am Haselbach. 45 records from Georgs-Padd (Wangerooge). 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 8 records from Krittenhorster Wald (Ostkilver). 23 records from Wattuntersuchung (Cuxhaven). 34 records from Wattenmeer-Safari (Wurster Watt). 17 records from Tierpark Zittau. 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 15 records from Tiere. 7 records from Stadtrandlandschaft Apolda-Nord. 135 records from Waldi-Weiher. 61 records from BIRDRACE Baumläufer. 15 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 1 records from Graureiher in Lans. 42 records from Kleinstbiotop mit Schulteich/Weißwasser. 6 records from Sächsische Schweiz (Pfaffenstein). 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 94 records from Landschaftsschutzgebiet Buchhorst 4. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 12 records from Schulgelände Erich-Kästner-Schule. 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 91331 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 1120 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 152 records from BIRDRACE NAJU-Aspach. 709 records from Upper Silesian Museum, Bird Collection. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 15 records from Bodentiere rund um die Schule. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 13 records from Warnowufer Groß Klein. 16 records from Im und um das Schulhaus. 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 40 records from Tiere und Pflanzen um uns herum !. 27 records from Bäche im Mooswald (Vörstetten). 17 records from Kohlbach (Sulzfeld). 24 records from Tauchen und Meer. 18 records from Naturtag. 15 records from Kirchheller Heide ( Bottrop). 10 records from Bachpatenschaft Beeke. 12 records from Ohemoor (Hamburg/Norderstedt). 4 records from Sächsische Schweiz (Wehlener Gebiet). 15 records from Urwald 2 (Bad Waldsee). 8 records from Eichendorf Weiher Schwalbach a.Ts.. 2 records from LSG Saale, Rößewiesen (Bernburg/Saale). 6717 records from LSUMZ Mammal Tissues. 3 records from Blankenfelder See. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 1 records from Haslauer Moor. 4 records from Neues Testprojekt. 21 records from LBV-Kindergruppen Markt Tussenhausen. 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 5 records from Schulinnenhöfe (Gelsenkirchen). 1 records from Fledermäuse über der Alster (Hamburg). 295 records from (Table 3) Range chart of benthic and planktonic foraminifera of ODP Site 127-795. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 107 records from Müritz-Nationalpark. 52 records from Naturschutzstation Weinberghaus (Dessau). 93 records from Haarbach Höfe. 6 records from Boimstorfer Sundern. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 555 records from FFH-Gebiet "Calwer Heckengäu". 89 records from Schulgelände Paul-Gerhardt-Schule. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 13 records from Tag der Artenvielfalt am Bruckenwasen. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 169 records from Expedition "Schulgelände". 274 records from Bernhardsthal. 161 records from BIRDRACE Nord-Seh-Team. 369 records from BIRDRACE Havelland. 145 records from BIRDRACE Dith Marsh Sandpiper. 144 records from BIRDRACE Die Mohrenlerchen. 254 records from BIRDRACE Thüringer Becken-Birders. 103 records from BIRDRACE federleser. 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 2 records from Hildener Heide - Spörkelnbruch (Haan). 163 records from Tiere und Pflanzen am Pfannenbach. 1 records from Karpfenteich, Klasse 6d. 1 records from 5. Wiener Gemeindebezirk. 5 records from Fledermäuse u. nachtaktive Insekten. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 1462 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 16006 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 80 records from Landschaftsschutzgebiet Schmutterwald. 371 records from Bannwald Burghauser Forst. 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 61 records from Fürstenberger Ralley Teil 3. 15 records from Kühnauer Aue und Kühnauer See. 359 records from Pöhlberg bei Annaberg. 1506 records from (Appendix C) Benthic foraminifera extinction group species in combined ODP Site 162-980 and DSDP Site 80-548. 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 146 records from LK 11 im Mönchspark. 278 records from BIRDRACE Usedommeln. 272 records from BIRDRACE Niederlausitz-Team. 287 records from BIRDRACE Pody und Co. 157 records from BIRDRACE Rheinische Wasserrallen. 98 records from BIRDRACE Die Paradiesvögel. 102 records from BIRDRACE Westfälische Nachtigallen. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 121 records from BIRDRACE Immerwiederhopf. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 1314 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 517 records from Schulzentrum "Parc Hosingen". 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 269 records from BIRDRACE Kosmos-Racer. 274 records from BIRDRACE Asiola-Quartett. 139 records from BIRDRACE Turbine Untersee. 256 records from BIRDRACE Upupa epöpse. 69 records from BIRDRACE Pfeifenten. 140 records from BIRDRACE Guckers Offenbach. 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 118 records from BIRDRACE Die Lippegeier. 80 records from BIRDRACE Falkenberger Fluppis. 166 records from BIRDRACE Die Düsselmöwen. 95 records from BIRDRACE BiBi. 96 records from BIRDRACE Emslandracer. 99 records from BIRDRACE TEAM BO-BACHTER. 260 records from (Table T5) Biogenic and mineral composition of sediments cored in Westerland, Sylt. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 106 records from VFD-RP: Eifel: Orchideenweide Ankly. 366 records from Weinberg Reichersdorf. 126 records from Schulwald Marksuhl. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 313 records from BIRDRACE Gätkes Erben. 279 records from BIRDRACE Wannacks Topti(c)ker. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 138 records from BIRDRACE Arkonauten. 258 records from BIRDRACE Raumpatrouille Oriolus. 1 records from Murcia ephippiata. 65 records from BIRDRACE Federal Birds of Investigation FBI. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 78 records from BIRDRACE leucorhö statt logorrhö. 82 records from BIRDRACE Die Ziegeneier. 82 records from BIRDRACE Buteo2DO. 84 records from BIRDRACE Bielefinken. 91 records from BIRDRACE NABU LV Hessen. 91 records from BIRDRACE SchrägeVögel. 95 records from BIRDRACE accipiter hardcore birding. 96 records from BIRDRACE OAG Neuwerk. 100 records from BIRDRACE Stuttgart 100 trööt. 105 records from BIRDRACE Kiesmätze. 174 records from BIRDRACE Bon(n)apartemöwen. 84 records from BIRDRACE Avinauten. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 108 records from BIRDRACE Diesmal sehen wir mehr. 402 records from Tag der Artenvielfalt in Heidelberg. 40 records from BUND Naturschutzzentrum St. Julian. 88 records from Abundance of benthic foraminifera in late Paleocene to eraly Pliocene sediments of DSDP Hole 74-525A on the Walvis Ridge, South Atlantic (Table 1). 442 records from Inventaire National du Patrimoine Naturel : CBN Brest. 97 records from BIRDRACE NABUhu Trier!. 132 records from BIRDRACE Die Wetterauer. 126 records from BIRDRACE Duckehühnchen. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 61 records from Wälder im Hainbachtal. 36 records from Liether Park 1 (LMS), Klasse 5b. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 102 records from BIRDRACE Buteo1DO. 103 records from BIRDRACE Die Otzberger. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 120 records from BIRDRACE The early birds. 119 records from BIRDRACE Tick, Trick und Track. 115 records from BIRDRACE Die UHULOGEN. 114 records from BIRDRACE VIE will rock you!. 112 records from BIRDRACE Gütersloher Gimpel. 109 records from BIRDRACE Die Borner. 4500 records from (Figure 7) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-540. 107 records from BIRDRACE Herford Birders. 44 records from Wiesen am Treffpunkt Freizeit. 66 records from Langes Tannen(LMS), Klasse 5d. 101 records from BIRDRACE Enger am Spektiv. 102 records from BIRDRACE Willi goes Birding. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 104 records from BIRDRACE Erlanger Piepmätzchen. 158355 records from All Ireland Non-Marine Molluscan Database. 105 records from BIRDRACE coesfelder_vogelkundler. 106 records from BIRDRACE Ave Goettingen!. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 60102 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 111 records from BIRDRACE Die Wendehälse. 110 records from BIRDRACE Angeliter Ornis. 107
Keywords: GBIF; biodiversity; species occurrences